Definitive Local Therapy for Oligo-recurrence in Patients With Completely Resected Non–small Cell Lung Cancer. (March 2020) - Matsuguma, Haruhisa; Nakahara, Rie; Wakamatsu, Ikuma; Kishikawa, Takayuki; Sugiyama, Tomohide; Nakamura, Yoichi; Kasai, Takashi; Kamiyama, Yukari; Hoshi, Nobuo; Inoue, Koichi; Katano, Susumu; Yokoi, Kohei
Abstract : Background: The aim of this study was to elucidate a curable subgroup among patients with non–small cell lung cancer (NSCLC) who developed postoperative recurrence. Patients and Methods: Between 1986 and 2012, among the 1408 patients who underwent complete anatomic lung resection for NSCLC at our institution, 420 developed recurrence. After excluding 14 patients with insufficient information about recurrence, 406 were included in this retrospective study. We investigated the association between several clinicopathologic factors and postrecurrence overall survival (PR-OS) and postrecurrence progression-free survival (PR-PFS). Results: The 5-year PR-OS and PR-PFS rates were 14.0% and 5.9%, respectively. By multivariate analysis, female sex, longer disease-free interval, specific targeted therapy, recent recurrence, oligo-recurrence, and definitive local therapy (DLT) were found to be independent favorable prognostic factors for both PR-OS and PR-PFS. Among these 6 prognostic factors, although female sex, longer disease-free interval, and specific targeted therapy were associated with a prolonged median PR-PFS time, they were not associated with an improved 5-year PR-PFS rate. In contrast, recent recurrence, oligo-recurrence, and DLT were associated with improvement in both the median PR-PFS time and 5-year PR-PFS rate. Conclusions: We found that recent recurrence, oligo-recurrence, and DLT were associated with an improved median PR-PFS time and long-term PR-PFS rate in patients with postoperative recurrence after complete resection of NSCLC. On the basis of these results, we believe that DLT should be considered first for patients with oligo-recurrence before applying noncurative treatment.